Burnout in adolescent elite athletes. A pilot study on an Austrian student sample - Schorb, A.; Aichhorn, J.; Schiepek, G.; Aichhorn, W. (Sports Psychiatry, 2023)
Abstract:Objectives: Adolescent elite athletes are generally exposed to considerable stress. This study investigated the extent and intensity of burnout in adolescent athletes attending an elite Austrian sports school. Methods: The German version of the Athlete Burnout Questionnaire (ABQ) and additional questions on burnout-related risk factors were applied to a sample of 63 students. Results: The data show a substantial burden of burnout in the student sample, compared to a sample of adult endurance athletes. Burnout was negatively associated with training duration and with a perspective onto a professional sports career, and positively associated with thoughts about finalizing sports, with the number of injuries, and with high levels of success-related psychic pressure. Conclusions: Burnout in adolescent elite athletes at an Austrian sports school was evident in number and severity. Psychological factors like doubts on the career, perceiving a professional perspective in sports, self-efficacy, or sense-making may interact with contextual factors in a circular way.